2022
DOI: 10.1029/2022gl100053
|View full text |Cite
|
Sign up to set email alerts
|

Improving the WRF Forecast of Landfalling Tropical Cyclones Over the Asia‐Pacific Region by Constraining the Cloud Microphysics Model With GPM Observations

Abstract: We proposed a method to improve the forecasts of landfalling tropical cyclones (LTCs) by constraining the “cloud physics” with Global Precipitation Measurement (GPM) satellite observations. Eight typical LTCs that are well observed by GPM satellite in the Asia‐Pacific region from 2015 to 2021 are selected to verify the feasibility of this method. Using a cloud‐resolving model, the LTCs are simulated for 3 days with both the original and modified microphysics scheme for comparison. The improvement of LTC foreca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…(2018) concluded that raindrops tend to be more spherical in typhoon systems based on statistics of ARs from 2DVD raw products. Given the current interest in unraveling the internal kinematics and microphysics of tropical cyclones with polarimetric and dual‐frequency observations (Bao et el., 2022; Didlake Jr. & Kumjian, 2018; Feng & Bell, 2019; Homeyer et al., 2021; Huang et al., 2022; Wu, Zhang, Xie, et al., 2022; Wu, Zhang, Zhang, et al., 2022; Zhao et al., 2019), there is a need for accurate AR parameterizations that bridge those observations and raindrop size distributions. Therefore, the necessity of pinning down an AR parameterization from 3D retrievals appears to be more urgent in tropical cyclones.…”
Section: Introductionmentioning
confidence: 99%
“…(2018) concluded that raindrops tend to be more spherical in typhoon systems based on statistics of ARs from 2DVD raw products. Given the current interest in unraveling the internal kinematics and microphysics of tropical cyclones with polarimetric and dual‐frequency observations (Bao et el., 2022; Didlake Jr. & Kumjian, 2018; Feng & Bell, 2019; Homeyer et al., 2021; Huang et al., 2022; Wu, Zhang, Xie, et al., 2022; Wu, Zhang, Zhang, et al., 2022; Zhao et al., 2019), there is a need for accurate AR parameterizations that bridge those observations and raindrop size distributions. Therefore, the necessity of pinning down an AR parameterization from 3D retrievals appears to be more urgent in tropical cyclones.…”
Section: Introductionmentioning
confidence: 99%
“…The above results also imply the significance of improving the model parameterization of large particles, as cloud microphysics models generally overproduce small particles in TC forecast due to unrealistic melting processes (Wu et al., 2022). In addition, around the melting layer, the “bright band” signature in Z e is more distinct as typhoon rapidly intensifies, especially in the peripheral rainbands region (250–300 km).…”
Section: Resultsmentioning
confidence: 88%
“…To better showcase the performance of our model, we select two natural disasters, typhoon and heatwave, for visual anal- RQE (-underestimate, + overestimate) SEDI (the closer to 1 the better) Exloss Diffusion ExEnsemble t2m u10 q500 u500 t2m@90th t2m@99.5th ws10@90th ws10@99.5th ysis. Specifically, we choose the Nanmadol typhoon (Wu et al, 2023) at 6:00 on September 17, 2022, and the heatwave in the southeastern coastal area of China at 12:00 on August 14, 2022 (Jiang et al, 2023), for three-day forecast and visualization. Figure 7 illustrates the results, with the two rows showing surface wind speed and surface temperature, respectively.…”
Section: Case Analysismentioning
confidence: 99%